A.S.P.E.N. Standards for Nutrition Support: Home and Alternate Site Care. (August 2014) - Durfee, Sharon M.; Adams, Stephen C.; Arthur, Elaine; Corrigan, Mandy L.; Hammond, Kathleen; Kovacevich, Debra S.; McNamara, Kevn; Pasquale, Jack A.
The American Society for Parenteral and Enteral Nutrition (A.S.P.E.N.) is a professional society of physicians, nurses, dietitians, pharmacists, nurse practitioners, physician assistants, other allied health professionals, and researchers. A.S.P.E.N. envisions an environment in which every patient receives safe, efficacious, and high-quality nutrition care. A.S.P.E.N.'s mission is to improve patient care by advancing the science and practice of clinical nutrition and metabolism. These combined Standards for Nutrition Support: Home Care and Alternate Site Care are an update of the 2005 and 2006 standards.